1999
DOI: 10.1055/s-1999-22
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ligation and Sclerotherapy Versus Ligation Alone for Eradication of Bleeding Esophageal Varices: A Randomized and Prospective Trial

Abstract: Since ligation combined with low-volume sclerotherapy did not reduce the time required for variceal eradication, it can be concluded that the combined therapy is not superior to ligation alone. This mode of endoscopic therapy for the treatment of bleeding esophageal varices is therefore not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 14 publications
2
14
1
1
Order By: Relevance
“…Our study demonstrated an overall re-bleeding rate in a real-world clinical practice over a 2-year period of 4.6%, which is markedly lower than previous reports with standard clinical practice [4,15,16,[23][24][25][26][27][28][29]. Other studies suggest a re-bleeding rate of 17.2% during the first 12 months following sentinel bleed among patients undergoing band ligation in conjunction with b-blockers for secondary prevention [30], although Includes one patient who suffered a fatal re-bleeding event.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Our study demonstrated an overall re-bleeding rate in a real-world clinical practice over a 2-year period of 4.6%, which is markedly lower than previous reports with standard clinical practice [4,15,16,[23][24][25][26][27][28][29]. Other studies suggest a re-bleeding rate of 17.2% during the first 12 months following sentinel bleed among patients undergoing band ligation in conjunction with b-blockers for secondary prevention [30], although Includes one patient who suffered a fatal re-bleeding event.…”
Section: Discussioncontrasting
confidence: 68%
“…EBL is used to reduce the mortality from esophageal variceal re-bleeding; however, death rates among patients undergoing standard EBL remain elevated, and reported re-bleeding rates range from approximately 10% [15] to greater than 50% [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Others prefer injecting the sclerosant between the banded sites. It should be remembered that these approaches may not be superior to band ligation alone Saeed et al 1997;Djurdjevic et al 1999;Garg et al 1999) (Table 3).…”
Section: Combination Of Band Ligation and Sclerotherapymentioning
confidence: 99%
“…Certains auteurs font une prémédication avec 5 mg de diazépam [6], d'autres associent le diazépam au midazolam [7] avec ou sans mépé-ridine [8,9]. Le recours à une anesthésie locale à la xylocaïne à 8 % a parfois été signalé [2,10]. En France, les séances de ligature sont souvent réalisées sous anesthésie générale [1].…”
Section: Déroulement Des Séancesunclassified